If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(P + 8) = q Reorder the terms: 0.5(8 + P) = q (8 * 0.5 + P * 0.5) = q (4 + 0.5P) = q Solving 4 + 0.5P = q Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 0.5P = -4 + q Combine like terms: 4 + -4 = 0 0 + 0.5P = -4 + q 0.5P = -4 + q Divide each side by '0.5'. P = -8 + 2q Simplifying P = -8 + 2q
| f(x)=15-1 | | 2m+2n-5= | | 4x+32=20x | | 3x+1=-3x+31 | | ln(x^2)=9 | | -5/8+83/8= | | 4p+8-3p= | | 750+8=758 | | 28=(3x+4)*4 | | 4x+-2=2(x+-6) | | 3(2x+5)=ax+5 | | 4(5x+2)-6x=5(2x+4) | | 60X=0.1 | | 6(8+x)=78 | | 4x-6x=2x | | 9(2n-5)=(9n+7)+8 | | 61x^2+56x+4=0 | | -2x+4=4x+16 | | (x-15)(x+3)=0 | | 7(12+y)=4 | | 3t+10=16 | | 3/5n-10=2/5n | | -42=4v-8 | | 5/x-3/5=20 | | 6x+5+7x=34 | | -11b+5+9b=-3b+10 | | 6X+48Y+8Z=2400 | | 20=(150+20p)-(10+30p) | | 61-6x=-11 | | 3y-2=3(2+y) | | (4-3i)(5+i)=0 | | 2n-3(4n+5)=-6+17 |